The Impact of Work Environment, Work Discipline, and Leadership on Employee Performance at PT Vorindo Teknologi Indonesia. - Sugandha Sugandha; Suhendar Janamarta; Fidellis Wato Tholok; Donny Yana (Science: Indonesian Journal of Science, 2025)
Employees are the primary valuable asset for a company that needs to be well-maintained. Therefore, both the company and the employees must collaborate, one way being the implementation of a positive work environment to foster discipline in carrying out tasks, ultimately leading to a significant improvement in performance. The research utilizes various data analysis methods, including validity testing, descriptive analysis, and hypothesis testing. The analysis revealed that the organizational work environment positively and significantly influences employee performance. Furthermore, work discipline also demonstrates a strong positive impact on performance, as does leadership style, which similarly plays a crucial role in enhancing employee effectiveness.This research aims to examine how organizational culture, work discipline, and leadership influence performance. The method used is information collection through the distribution of surveys to participants. The analysis results indicate that the work environment, work discipline, and leadership significantly affect performance, evidenced by t-count values that exceed t-table values (2.049 for the organizational work environment, 2. 269 for work discipline, and 3. 892 for leadership, compared to a t-table value of 1. 660). Furthermore, the probability level of these results is below 0. 05, and the multiple determination coefficient reaches 42. 6% concerning performance.